Epilepsy With Suicide: A Bibliometrics Study and Visualization Analysis via CiteSpace - Guo, Yi; Xu, Zheng-Yan-Ran; Cai, Meng-Ting; Gong, Wen-Xin; Shen, Chun-Hong (Frontiers in Neurology, 2022)
Objective: The purpose of this study was to analyze the research status of epilepsy with suicide and to determine the hotspots and frontiers via CiteSpace. Method: We searched the Web of Science Core Collection (WoSCC) for studies related to epilepsy and suicide from inception to September 30, 2021. We used CiteSpace to generate online maps of collaboration between countries, institutions, and authors, and revealed hot spots and frontiers in epilepsy with suicide. Results: A total of 631 publications related to epilepsy with suicide were retrieved from the WoSCC. Andres M. Kanner was the most published author (25 papers). The USA and Columbia University were the leading country and institution in this field, with 275 and 25 papers, respectively. There were active cooperation between institutions, countries, and authors. Hot topics focused on depression, antiseizure medications, pediatric epilepsy, and risk factors of suicide in patients with epilepsy (PWEs). Conclusions: Based on the CiteSpace findings, this study detected active collaboration among countries, institutions and authors. The main current research trends include suicide caused by depression, suicide caused by the use of antiseizure medications, suicide in children with epilepsy, and risk factors for suicide in PWEs. Thus, more attention should be paid to the psychiatric comorbidity of PWEs (especially pediatric epilepsy), the suicidal tendency of PWEs, and the rational use of antiseizure medications in the future.